2015
DOI: 10.1039/c5sc00754b
|View full text |Cite
|
Sign up to set email alerts
|

Azasugar inhibitors as pharmacological chaperones for Krabbe disease

Abstract: Modified azasugar molecules have been synthesized and characterized as excellent pharmacological chaperone candidates to treat the neurodegenerative disorder Krabbe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 87 publications
0
42
0
Order By: Relevance
“…Thus, for this mutation, the chaperoning effect conferred by α‐lobeline might have been specific to the newly introduced glycan. In support of this, it was observed that α‐lobeline does not confer any increase in thermal stability to WT GALC and may also explain why it did not have a chaperoning effect on the other GALC variants tested (W.C. Lee et al, ; Hill et al, ).…”
Section: Identifying Candidate Mutations For Pctmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, for this mutation, the chaperoning effect conferred by α‐lobeline might have been specific to the newly introduced glycan. In support of this, it was observed that α‐lobeline does not confer any increase in thermal stability to WT GALC and may also explain why it did not have a chaperoning effect on the other GALC variants tested (W.C. Lee et al, ; Hill et al, ).…”
Section: Identifying Candidate Mutations For Pctmentioning
confidence: 89%
“…In the work published to date, a range of different substrates has been used to monitor GALC activity, including tritiated GalCer (Biela‐Banas et al, ), alkylated fluorogenic and colorimetric substrates such as 2‐hexadecanoylamino‐4‐nitrophenyl‐β‐D‐galactopyranoside (HNG; W.C. Lee et al, ) and 6‐hexadecanoylamino‐4‐methylumbelliferyl‐β‐D‐galactopyranoside (HMG; Ribbens et al, ; Berardi et al, ; Hossain et al, ), and water‐soluble fluorogenic and colorimetric substrates such as 4NBDG (Hill et al, ) and 4MBDG (Martino et al, ).…”
Section: Methods For Monitoring the Effectiveness Of Chaperonesmentioning
confidence: 99%
“…Under chemical profile, azasugars and iminosugars were tested as GALC inhibitors and as PCs. Specifically, Hill and coworkers () identified some chemical characteristics that, associated with azasugar compound, are required for PC specificity and pH‐dependent affinity for GALC. This work was made possible by recent studies on not only the structures of GALC but also the mode of binding of substrate, intermediate, and product to the enzyme active site, accompanied by conformational changes of active site residues (Deane et al, ; Hill et al, ).…”
Section: Chaperones For Kd: Preclinical Studiesmentioning
confidence: 99%
“…oryzae, o-nitrophenyl β-D-galactopyranoside for β-galactosidase from E. coli, p-nitrophenyl β-D-glucopyranoside for almond β-glucosidase, p-nitrophenyl α-D-glucopyranoside for yeast α-glucosidase and p-nitrophenyl α-D-galactopyranoside for green coffee beans α-galactosidase) at six concentrations ranging from 1/4K m up to 4 K m monitoring at 400 nm with A < 1 using a Varian Cary 100 Bio UV-vis spectrophotometer. Methyl 3,4-di-O-benzyl-2-benzyloxymethyl-2-deoxy-α/β-D-allopyranoside (14). For experiments with preincubation, enzyme and inhibitor were mixed 30 min prior to addition of substrate.…”
Section: Inhibition Studiesmentioning
confidence: 99%